Multiple stable isotope fronts during non-isothermal fluid flow. (15th February 2018) - Fekete, Szandra; Weis, Philipp; Scott, Samuel; Driesner, Thomas
Abstract: Stable isotope signatures of oxygen, hydrogen and other elements in minerals from hydrothermal veins and metasomatized host rocks are widely used to investigate fluid sources and paths. Previous theoretical studies mostly focused on analyzing stable isotope fronts developing during single-phase, isothermal fluid flow. In this study, numerical simulations were performed to assess how temperature changes, transport phenomena, kinetic vs. equilibrium isotope exchange, and isotopic source signals determine mineral oxygen isotopic compositions during fluid-rock interaction. The simulations focus on one-dimensional scenarios, with non-isothermal single- and two-phase fluid flow, and include the effects of quartz precipitation and dissolution. If isotope exchange between fluid and mineral is fast, a previously unrecognized, significant enrichment in heavy oxygen isotopes of fluids and minerals occurs at the thermal front. The maximum enrichment depends on the initial isotopic composition of fluid and mineral, the fluid-rock ratio and the maximum change in temperature, but is independent of the isotopic composition of the incoming fluid. This thermally induced isotope front propagates faster than the signal related to the initial isotopic composition of the incoming fluid, which forms a trailing front behind the zone of transient heavy oxygen isotope enrichment. Temperature-dependent kinetic rates of isotope exchange between fluid and rock strongly influence the degree of enrichment at the thermal front. In systems where initial isotope values of fluids and rocks are far from equilibrium and isotope fractionation is controlled by kinetics, the temperature increase accelerates the approach of the fluid to equilibrium conditions with the host rock. Consequently, the increase at the thermal front can be less dominant and can even generate fluid values below the initial isotopic composition of the input fluid. As kinetics limit the degree of isotope exchange, a third front may develop in kinetically limited systems, which propagates with the advection speed of the incoming fluid and is, therefore, traveling fastest. The results show that oxygen isotope signatures at thermal fronts recorded in rocks and veins that experienced isotope exchange with fluids can easily be misinterpreted, namely if bulk analytical techniques are applied. However, stable isotope microanalysis on precipitated minerals may – if later isotope exchange is kinetically limited – provide a valuable archive of the transient thermal and hydrological evolution of a system.